PROFESSIONAL EXAMINATIONS: ACCOUNTING PRACTICE. - Chamberlain, John H. (The Accounting Review, 1961)
The article presents several problems related to accounting, which were prepared by the Board of Examiners of the American Institute of Certified Public Accountants and were presented as the second half of the C.P.A. examination in accounting practice on May 18, 1961. One of the problem focuses on matters related to the purchase of property by a certain corporation. It discusses the issue of appraised value of a property, depreciation accounting, interest rates, and profit and loss analysis in the deal. Another problem focuses on a company ABC, who has acquired all of the outstanding stock of XYZ Corp. Now ABC gave the stockholders of XYZ certain amount of cash and shares of previously unissued common stock in exchange for all the outstanding stock of XYZ. Students have been asked to prepare the journal entry of ABC to record its investment in XYZ, and explain the basis for the value assigned to the investment. A question has been presented which discusses issues related to partnerships. students have been assigned to prepare statement which contains a detailed explanation of the difference between actual costs and standard costs.